Green chemistry teaching: Belarusian view through world tendencies - Savitskaya, Тatsiana A.; Liavontsyeu, Aliaksei P.; Kimlenka, Iryna M.; Grinshpan, Dmitry D.; Drashar, Pavel; Lam, Tran Dai; Lan, Pham Thi (Journal of the Belarusian State University. Chemistry, 2022)
The disciplines curricula on green chemistry and sustainable chemistry available in various universities of the world were analysed. Trends in education development and science in this particular area were described as well as actual green chemistry teaching problems that need to be solved. Analysing the data obtained three approaches defining a trajectory for teaching the basic foundations of green chemistry were identified: British, European, and American. The first one involves in-depth study and the formation of competencies in the field of green chemistry. The second approach implies the inclusion of green chemistry in traditional chemical disciplines (organic, analytical chemistry, etc.). The third approach implies the inclusion of green chemistry as a module in such practice-oriented disciplines as biotechnology, food safety, ecology, etc. The content of the laboratory classes in green chemistry curricula and the usage of a green chemistry metric «green star» for assessment of their safety are discussed. It is proposed to join efforts of different countries for green chemistry ideas promotion and transfer the green chemistry ideas through creation of green chemistry centers of excellence for the use of its principles and methods in scientific research and the educational process.
Keywords: green chemistry; sustainable chemistry; curricula; safe laboratory classes; centers of excellence